2004
DOI: 10.1007/s00280-004-0865-3
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of 17-demethoxy 17-[[(2-dimethylamino)ethyl]amino]geldanamycin (17DMAG, NSC 707545) in C.B-17 SCID mice bearing MDA-MB-231 human breast cancer xenografts

Abstract: Plasma pharmacokinetics of 17DMAG in tumor-bearing mice were similar to those previously reported in nontumor-bearing mice. 17DMAG was distributed widely to tissues but was retained for longer in tumors than normal tissues. Raf-1, HSP90, and HSP70 were altered to different degrees in tumors, livers, and kidneys of 17DMAG-treated animals. These data illustrate the complex nature of the biological responses to 17DMAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 46 publications
3
106
1
Order By: Relevance
“…Blockade of the ATPase activity of Hsp90 have effectively inhibited cell signaling molecules in proliferating cancer cells (43). However, geldanamycin and its derivatives have some significant limited pharmaceutical properties as well as toxicities in clinical trials (14,44). For these reasons, the development of novel Hsp90 inhibitors has been an area of intense research.…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of the ATPase activity of Hsp90 have effectively inhibited cell signaling molecules in proliferating cancer cells (43). However, geldanamycin and its derivatives have some significant limited pharmaceutical properties as well as toxicities in clinical trials (14,44). For these reasons, the development of novel Hsp90 inhibitors has been an area of intense research.…”
Section: Discussionmentioning
confidence: 99%
“…53 Others have reported HSPs expressed in glomeruli and tubules of some SLE patients. 9 However, our assessment of HSP90 expression in our control and HSP90-inhibited groups as well as C57BL/6 mouse kidneys showed that the diseased mice exhibited elevated HSP90 in tubules but not in glomeruli.…”
Section: Mature B Cells Were Decreased In Mice Treated With 17-dmagmentioning
confidence: 99%
“…We selected 17-DMAG over GA as our in vivo inhibitor based on published results showing reduced hepatotoxicity in vivo when compared to GA or 17-allylamino-17-demethoxygeldanamycin (17-AAG). 16,18,53,54 Dosages were selected based on studies showing effective treatment and minimal toxicity at dosages under 15 mg/kg administered 3 days per week for 3 weeks. 55 We injected MRL/lpr mice with 17-DMAG 3 days a week on alternating days for 6 weeks, (a) Linear regression of grouped proteinuria scores showed control mice exhibited increased proteinuria, while mice treated with 17-DMAG did not increase in proteinuria.…”
Section: Hsp90 Inhibition Reduced Inflammatory Mediator Production Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, direct inhibition of HSP90 may have a much more profound effect on arsenite sensitivity and centrosome regulation than preventing induction of HSP70i. A375, HeLa and TR9-7 (p53 (-) ) cells were plated in 96 well dishes and treated for up to 3 days with 0-300 nM 17-DMAG (a potent inhibitor of HSP90 ATPase activity, (Eiseman et al, 2005)) combined with either 0, 0.5, 1, 2.5 or 5 ÎŒM arsenite. Viability was measured using AlamarBlue after 48 h of treatment ( Figure 6).…”
Section: Disruption Of Hsp70/hsp90 Activity Enhances Effectiveness Ofmentioning
confidence: 99%